2022
DOI: 10.1111/1462-2920.15964
|View full text |Cite
|
Sign up to set email alerts
|

The Bacillus phage SPβ and its relatives: a temperate phage model system reveals new strains, species, prophage integration loci, conserved proteins and lysogeny management components

Abstract: The Bacillus phage SPβ has been known for about 50 years, but only a few strains are available. We isolated four new wild-type strains of the SPbeta species. Phage vB_BsuS-Goe14 introduces its prophage into the spoVK locus, previously not observed to be used by SPβ-like phages. Sequence data revealed the genome replication strategy and the genome packaging mode of SPβ-like phages. We extracted 55 SPβlike prophages from public Bacillus genomes, thereby discovering three more integration loci and one additional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 95 publications
1
20
0
Order By: Relevance
“…Phage genomes were sequenced with an Illumina MiSeq-system (2 × 300 bp) as described previously ( Kohm et al, 2022 ). RNA samples were reverse transcribed to dsDNA in vitro and sequenced like dsDNA samples with an Illumina MiSeq-system (2 × 300 bp) as described previously ( Kohm et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Phage genomes were sequenced with an Illumina MiSeq-system (2 × 300 bp) as described previously ( Kohm et al, 2022 ). RNA samples were reverse transcribed to dsDNA in vitro and sequenced like dsDNA samples with an Illumina MiSeq-system (2 × 300 bp) as described previously ( Kohm et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Two recent studies uncovered several novel players of the SPβ lysis-lysogeny decision system [Brady et al, 2021; Kohm et al, 2022]. For instance, a suppressor analysis with a SPβ aimR mutant, which generates more lysogenic cells, revealed that the spontaneous inactivation of the yopN gene, encoding a protein of unknown function, partially restores the control of lysis-lysogeny [Brady et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, a suppressor analysis with a SPβ aimR mutant, which generates more lysogenic cells, revealed that the spontaneous inactivation of the yopN gene, encoding a protein of unknown function, partially restores the control of lysis-lysogeny [Brady et al, 2021]. The same studies identified YopR as the master repressor of the lytic cycle of SPβ [Brady et al, 2021; Kohm et al, 2022]. Although it is unclear how AimR, YopN and YopR interact with each other, it has been proposed that YopN stimulates the repressor activity of YopR [Brady et al, 2021].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations